2022
DOI: 10.3389/fpsyg.2022.879156
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Cues Modulate Children’s and Adults’ Processing of Audio-Visual Face Mask Speech

Abstract: During the COVID-19 pandemic, questions have been raised about the impact of face masks on communication in classroom settings. However, it is unclear to what extent visual obstruction of the speaker’s mouth or changes to the acoustic signal lead to speech processing difficulties, and whether these effects can be mitigated by semantic predictability, i.e., the availability of contextual information. The present study investigated the acoustic and visual effects of face masks on speech intelligibility and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 79 publications
1
14
0
2
Order By: Relevance
“…A similar approach could be used in establishing the effects of masks on children's ability to read others‘ facial expressions and process speech. The literature has been variable, with some studies implying a significant impact on children and others implying a negligible effect 27,28,30,34,37,39,50,53,55,56,60,64 . Interestingly, while Ruba et al 53 found that children were slightly more accurate in inferring emotions when faces were uncovered, compared with when reviewing pictures of faces with masks, there was no difference in their accuracy between faces with sunglasses and masks.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach could be used in establishing the effects of masks on children's ability to read others‘ facial expressions and process speech. The literature has been variable, with some studies implying a significant impact on children and others implying a negligible effect 27,28,30,34,37,39,50,53,55,56,60,64 . Interestingly, while Ruba et al 53 found that children were slightly more accurate in inferring emotions when faces were uncovered, compared with when reviewing pictures of faces with masks, there was no difference in their accuracy between faces with sunglasses and masks.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined one aspect of linguistic communication: spoken word recognition. Prior studies demonstrate that children do not show a mask detriment when they can leverage semantic knowledge, as in Schwarz et al, 2022. It is possible that other aspects of language learning, such as learning new words, are more constrained by the use of face masks.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is evidence that children may even be more resilient to masked communication than adults. For example, in a language comprehension task, children were better able to compensate for visual distortion caused by masks than adults (Schwarz et al., 2022). In sum, empirical evidence attesting to effects of masks on communication is not always consistent with preconceived notions about the impact of masks.…”
Section: Discussionmentioning
confidence: 99%
“…Yet this inquiry also appears of relevance to the wider field of second language acquisition (SLA) and applied linguistics, where research on L2 listening comprehension has shown benefits of visual speech cues in both laboratory and classroom contexts (e.g., Hardison, 1996Hardison, , 2003Sueyoshi & Hardison, 2005), and the role of visuals in language assessment is an area of active inquiry (for review, see Suvorov & He, 2022). Furthermore, from a more applied perspective, the wearing of face masks during the COVID-19 pandemic has drawn broader attention to the role of visual speech cues from the face during communicative interactions in general and in educational settings in particular (e.g., Schwarz et al, 2022). In the context of equity in education, understanding if and how students with lower proficiency in the language of instruction might be disproportionately influenced by teachers wearing face masks has practical implications for deciding to what extent such students may be in need of extra support.…”
Section: Introductionmentioning
confidence: 99%